Wind Turbine Design - โรยนรินทร์, วิรชัย (Frontiers in Engineering Innovation Research, 2005)
Mostly, the wind energy in Thailand is not practically recommended to use as the porwer resources to generate electricity compared with the European Countries. Nevertheless, in some particular areas, the positive results from the data recording unit are shown and can be recommended to use for the purposed. The wind energy is clean with environmental friendly and can be used as the power resource instead of fossil fuel. Additionally, the researchers can apply the basic and the principle of the momentum theorem which are mostly used in the wind engineering to study others renewable energy resource such as wave, hydro and marine current energy etc. This paper focuses in the details of the wind machine’s history and the basic engineering design of 5 kW wind machine